The Movement of Pure Hearts as the symbol and the road of maturing for pure love - Kluz, Marek (Kwartalnik Naukowy Fides et Ratio, 2022)
Destructive tendencies inside our civilisation affect the virtue of purity in an unprecedented way. Various arguments are being put forward against living a life in chastity. The life in purity is frequently associated with “rejection” of one’s own freedom. It is also argued that chastity is an element of an bygone era. For this reason the issue of sexual purity becomes currently a challenge – there is a need for a strong opposition against the distortions concerning the virtue of purity. For it is purity that provides for the maturing and deepening of love and prepares best for the bodily and spiritual union of woman and man in matrimony. Thus, it is essential to show the beauty and value of chastity. It has to be noted that the Church faithful to the teachings of Jesus Christ promotes all initiatives which in today’s world present chastity as a positive moral value. One of these initiatives is the Movement of Pure Hearts which through appropriate formation helps young people to fight for the purity of heart and body.